Crohn's disease in Blackpool--incidence and prevalence 1968-80. Issue 3 (March 1985) - Lee, F I; Costello, F T
Abstract : The occurrence of Crohn's disease has been studied in a population of approximately 300, 000 in Blackpool, a seaside town in the north of England, and the surrounding area. Between 1968 and 1980, 156 patients resident in the area were diagnosed as having Crohn's disease - an annual incidence of 4 per 10(5). For the years 1971-75, the incidence was 3.3 per 10(5) and for 1976-80 it was 6.1 per 10(5). The trend is upwards but there was an apparent fall in incidence in 1974-75. In 1979 there was a peak incidence of 8 per 10(5). Over the period of study, there was an increase in all three anatomical types, small intestinal, large intestinal, and mixed disease but this increase was most marked for purely large intestinal disease. Of the 156 cases, 35% had small intestinal disease at presentation, 35% had large intestinal disease and 30% had mixed disease. The overall sex ratio was female to male 1.89:1 but highest for large bowel disease -2.6:1. Analysis of age at presentation at different sites shows a unimodal distribution for small intestinal and mixed disease with a peak in the third and fourth decades. Large bowel Crohn's disease shows a bimodal distribution with peaks in the third and eighth decades. During the period of study we identified 185 cases of Crohn's disease in the study population. On 31 December 1980, 141 patients with the condition were living, a prevalence of 47 per 10(5).